1967
DOI: 10.1016/0031-9384(67)90053-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body temperature and water intake following intracerebral implantation of carbachol in rats

Abstract: HoLsr, S. G. T. AND D. DE WIED.Changes in body temperature and water intake following intracerebral implantation of carbachol in rats. PHYSIOL. BEHAV. 2 (4) [367][368][369][370][371] 1967.--Intracerebral carbachol produced a fall in core temperature in the rat when implanted in the area preoptica, the nucleus lateralis septi and the area between the thalamic nuclei and the nucleus ruber. Cholinergic stimulation of the anterohypothalamic region did not affect body temperature, while stimulation of the nucleus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1968
1968
1984
1984

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…To allow intracerebral application of the peptides, a stainless steel plate, equipped with 12 holes and with tubes attached to the holes, was fixed on the rat skull. Needles containing crystalline peptide at the tip can be inserted into the brain of the conscious rat through the tubes of the plate [Hulst and de Wied, 1967; van W imersma G reidanus and . After recovering from the operation the animals were reconditioned.…”
Section: Peptide Treatment A) Subcutaneous Administrationmentioning
confidence: 99%
“…To allow intracerebral application of the peptides, a stainless steel plate, equipped with 12 holes and with tubes attached to the holes, was fixed on the rat skull. Needles containing crystalline peptide at the tip can be inserted into the brain of the conscious rat through the tubes of the plate [Hulst and de Wied, 1967; van W imersma G reidanus and . After recovering from the operation the animals were reconditioned.…”
Section: Peptide Treatment A) Subcutaneous Administrationmentioning
confidence: 99%
“…Tubes, with a diameter of 0.8 ram, of the same material, protruding 2.50 mm from the lower side of the plate, were attached to the holes in the plate. This plate was fixed to the rat skull with dental cement (for details see [20]). Through the tubes needles of different length, containing crystalline substances at the tip, could be directed into the brain.…”
Section: Mater/ai~ and Methodsmentioning
confidence: 99%
“…In the rat hypothermia has been found following cholinergic stimulation of the anterior hypothalamus, lateral hypothalamus, preoptic region, nucleus lateralis septi and the area between the thalamie nuclei and the nucleus ruber [20,22,23,25]. In a previous study [20] it was suggested that cholinergically evoked drinking and hypothermia follow roughly parallel pathways in the limbic system and the diencephalon. As the fibre systems for these two phenomena need not necessarily be the same, further experiments were conducted to evaluate the previous results; these studies are reported here.…”
Section: Water Intakementioning
confidence: 97%
See 1 more Smart Citation
“…Since then abundant evidence has been obtained in support of this suggestion in a number of mammals by studying the effects of cholinomimetic substances on body temperature following their injection into the cerebral ventricles or into different regions of the hypothalamus. Experiments of this kind were done in mice (Friedman & Jaffe, 1969), rats (Hulst & de Wied, 1967;Meeter & Wolthuis, 1968;Myers & Yaksh, 1968;Lomax, Foster & Kirkpatrick, 1969;Meeter, 1969Meeter, , 1971Avery, 1972;Baird & Lang, 1973), sheep, goats and rabbits (Bligh, Cottle & Maskrey, 1971), cats (Baird & Lang, 1973) and monkeys (Myers & Yaksh, 1969). The nature of the thermoregulatory response to cholinomimetic substances was found to differ in different species and to be dependent on the dose of the substance injected, the ambient temperature, and when injected into the hypothalamus on the actual site of injection.…”
Section: Introductionmentioning
confidence: 99%